Avaliação da eficiência de uma boia submersa para geração de energia - Quintas, Raí Mariano (2019)
The threat of the global warming impacts has been encouraging the adoption of cleaner resources for energy generation, in opposition to the use of fossil fuels. An alternative that arises from this scenario is the wave energy. However, the energy produced by the wave energy converters, devices that converts wave energy into electricity, is still very expensive. Hence, it is interesting to make these devices more efficient, in order to cheapen the cost of the energy they produce. Therefore, this work proposes a strategy to control the ballast of the system in order to increase the hydrodynamic efficiency of the device. The ballast control aims to modify the system’s natural period so that it coincides with the period of the incident waves, increasing the overall energy of the system through the resonance effect. Numerical simulations were carried out using the SITUA-Prosim software and the results prove the efficiency of this strategy, opening space for further studies in this line of research.